Applied linguistics and second language teaching : an exploratory error analysis of the written English of Afrikaans-speaking std 6, 7, and 10 pupils at schools in four sociolinguistic areas - Ridge, Elaine (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ed.) -- University of Stellenbosch, 1983.